Persepsi Mahasiswa Terhadap Penggunaan Schoology sebagai Asesmen Online di Kelas Bahasa Inggris - Ida Megawati; Fauzan Aminudin; Endah Marwanti; Anni Nurul Hidayat; Ardian Arief; Abdul Rahim (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine students' perception of the use of Schoology as an online assessment in the English classroom and the benefits of using Schoology. This study uses a mixed methods approach that combines qualitative and quantitative data. Collecting data using questionnaires and interviews. Questionnaires were used to determine student perceptions using a five-point Likert Scale. Formal interviews were randomly assigned to 10 students. Questionnaire data were processed with SPSS version 21 and then triangulated and analyzed. Meanwhile, to determine the criteria for Respondent Achievement Level using the formula used by the Arikunto concept. The results of this study indicate that students have positive perceptions about assessment in English class through Schoology. Students are interested in using online assessments because online assessments are better than paper assessments. Students are attracted to the Schoology application because of its flexibility and ease of use. However, some students also stated that the use of online assessments in Schoology also presented a negative perception. Students can face problems with internet access, large data, and difficulty in managing time to do tests.